2020
DOI: 10.3390/polym12010136
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Electrochemical Performance and Stability of Polypyrrole by Polymerizing Ionic Liquids

Abstract: Polypyrrole (PPy) based electroactive materials are important building blocks for the development of flexible electronics, bio-sensors and actuator devices. As the properties and behavior of PPy depends strongly on the operating environment—electrolyte, solvent, etc., it is desirable to plant immobile ionic species into PPy films to ensure stable response. A premade ionic polymer is not optimal in many cases, as it enforces its own structure on the conducting polymer, therefore, polymerization during fabricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…PPyCDC revealed the best specific capacitance in this research with similar values found for CDC particles spray coated on a PVdF membrane [ 55 ] in the range of 31–39 F g −1 applied in the same solvent PC. Recent research [ 56 ] using electropolymerized PPy in combination with polymerized ionic liquids (PIL) forming PPyPIL films led to specific capacitance either in aqueous or organic electrolyte in the range of 75 F g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…PPyCDC revealed the best specific capacitance in this research with similar values found for CDC particles spray coated on a PVdF membrane [ 55 ] in the range of 31–39 F g −1 applied in the same solvent PC. Recent research [ 56 ] using electropolymerized PPy in combination with polymerized ionic liquids (PIL) forming PPyPIL films led to specific capacitance either in aqueous or organic electrolyte in the range of 75 F g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Electroctropolymerisation of Py and an ionic liquid monomer was carried out in order to obtain PPy with improved electrochemical properties [ 19 ]. The detailed analysis of products indicates that a blend of homopolymers was formed rather than a copolymer.…”
Section: Copolymerisation Of Pyrrolementioning
confidence: 99%
“…Taking into account the complex nature of electrochemical polymerisation and significant influence of the employed process conditions, different copolymer structures can be expected in the case of different pyrrole co-monomers, as shown in Scheme 2 . Based on the complex electropolymerisation mechanism, random [ 18 ] and block copolymers, graft copolymers, interpenetrating polymer blends [ 19 ], as well as complex systems of different products can be expected. This is reflected in the published works on pyrrole copolymers obtained not only by electrochemical, but also by chemical oxidative copolymerisation, in which copolymers with complex architectures were formed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PIL monomer synthesis is shown in the Supplementary Information, with the reaction given in Scheme S1 with the 1 HNMR signals shown in Figure S1, as has been reported in previous research [20]. The PIL monomer was poured into a Teflon mold and polymerized at 60 • C using an initiator (AIBN), with a reaction time of 36 h. The obtained PIL film was 80 ± 2 µm thick and was washed several times with ethanol to remove residual unreacted monomer and dried in an oven at 40 • C (2 mbar) for 24 h.…”
Section: Synthesis and Polymerization Of Polymerizable Ionic Liquid (Pil) Monomermentioning
confidence: 99%
“…This showed a specific capacitance of 12 F g −1 [46] while the protic PIL polymers from 1-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide, with few percentages of water, up to 3.8% [47], led to a specific capacitance in the range of 18 to 20 F g −1 , which showed that the addition of water reduced the electrochemical stability window. In most cases, PILs applied with the addition of deposited polypyrrole in the solid state showed a pseudo capacitance in the range of 5 F g −1 [48], while direct polymerization of pyrrole with PIL monomers reached 74 F g −1 [20]. Due to the differences in capacitance and electrochemical stability in the case of different electrolyte solvents, the sensor properties of the PIL films was investigated.…”
Section: Specific Capacitance Of Pil Films Applied At Electrolytes With Different Solventsmentioning
confidence: 99%